KEBUDAYAAN MAKKOMBONG DALAM KEHIDUPAN MASYARAKAT DI KECAMATAN MASALLE KABUPATEN ENREKANG - Arifin, Ibrahim (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
Makkombong tradition is a culture of mutual cooperation owned by the people of Enrekang district which has existed since ancient times and has been passed down from generation to generation to the next generation. Makkombong culture is the culture of the people of Enrekang district which is full of strong values ​​of togetherness. Where when someone holds a big event, other people in the community will definitely come and provide assistance without expecting anything in return from those who carry out or hold the activity or event. Even though in the makkombong culture, people never expect anything in return for the help they provide, it is a shame if they do not give any response to the help given to them by other people. However, as time goes by and the era of globalization begins to enter the Masalle sub-district community, the makkombong culture Even this also faded and was replaced by work with a salary system or what in the Enrekang Duri language is called Mangkande Gaji. The increasingly rapid development of globalization has resulted in increasingly sophisticated technological advances, opening up new opportunities and information flows that can be accessed by all communities, including in rural areas. Rural communities are starting to adopt global patterns by creating a more modern lifestyle such as a total transformation from traditional values ​​to more modern values.